Photochemical efficiency of basil cultivars fertigated with salinized nutrient solutions - Santos,Sandy T. dos (2020)
ABSTRACT Reduction in plant growth under salt stress is due, among other factors, to changes in photochemical efficiency and, consequently, in photosynthesis. The objective of this study was to evaluate the effect of salt stress on the chlorophyll fluorescence variables in cultivars of basil (Ocimum basilicum L.). The experiment was conducted in a greenhouse, using a randomized block design in a 5 x 3 factorial scheme, corresponding to five basil cultivars (‘Grecco a Palla’, ‘Alfavaca Basilicão’, ‘Alfavaca Verde’, ‘Lemoncino’ and ‘Roxo’) and three salinity of the nutrient solution (2.0, 3.5 and 5.0 dS m-1), with three repetitions, and the experimental plot was represented by three pots containing 3.0 dm3 of coconut fiber. At the full flowering stage, plants were evaluated for chlorophyll fluorescence, when adapted to the dark, as well as under saturating light conditions. In general, there were changes in fluorescence variables only at salinity above 3.5 dS m-1. Fertigation using high-salinity water promotes strong changes in the chlorophyll a fluorescence of sensitive basil cultivars. The cultivars ‘Grecco a Palla’ and ‘Alfavaca Verde’ were little affected by the increase of salinity, being the most tolerant to salt stress. In the cultivars ‘Alfavaca Basilicão’, ‘Lemoncino’ and ‘Roxo’, chlorophyll fluorescence was strongly affected by salinity, being the most sensitive. The tolerance ranking based on chlorophyll fluorescence is: ‘Grecco a Palla’ = ‘Alfavaca Verde’ > ‘Alfavaca Basilicão’ > ‘Lemoncino’ > ‘Roxo’.